2015
DOI: 10.1007/s00204-015-1622-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of putative reproductive toxicity of low-dose exposures to flutamide in Wistar rats

Abstract: The current investigation examines whether the model anti-androgenic substance flutamide is capable of disrupting endocrine homeostasis at very low doses. The data generated clarify whether a non-monotonic dose-response relationship exists to enhance the current debate about the regulation of endocrine disruptors. Moreover, it is part of a series of investigations assessing the dose-response relationship of single and combined administration of anti-androgenic substances. A pre-postnatal in vivo study design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…This is in line with more general evidence that thresholds do exist for endocrine-related effects (Borgert et al 2013;EFSA Scientific Opinion 2013;Borgert et al 2012;Caldwell et al 2012). The existence of threshold doses was recently also shown for the anti-androgenic drug flutamide in a pre-and postnatal in vivo study in Wistar rats (Fussell et al 2015). Underlying uncertainties in an appropriate hazard assessment of substances with an endocrine mode of action are probably more the result of inappropriate study designs and the omission of relevant parameter.…”
Section: Discussionsupporting
confidence: 82%
“…This is in line with more general evidence that thresholds do exist for endocrine-related effects (Borgert et al 2013;EFSA Scientific Opinion 2013;Borgert et al 2012;Caldwell et al 2012). The existence of threshold doses was recently also shown for the anti-androgenic drug flutamide in a pre-and postnatal in vivo study in Wistar rats (Fussell et al 2015). Underlying uncertainties in an appropriate hazard assessment of substances with an endocrine mode of action are probably more the result of inappropriate study designs and the omission of relevant parameter.…”
Section: Discussionsupporting
confidence: 82%
“…In the rat model, various substances have been administered to pregnant females to evaluate the impact on reproductive organ development in the offspring. [23,24,25]. When the pregnant female rat received flutamide (androgen receptor antagonist) or dibutylphthalate [24,25] the AGD at birth was shorter in male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24,25]. When the pregnant female rat received flutamide (androgen receptor antagonist) or dibutylphthalate [24,25] the AGD at birth was shorter in male offspring. Exposure to phthalates was also associated with a higher prevalence of cryptorchidism and hypospadias [24].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the single compound testing have been published previously, i.e. flutamide (Fussell et al 2015 ), prochloraz (Melching-Kollmuss et al 2017 ) and vinclozolin (Flick et al 2016 ). Here we report on the effects of combined exposure to all three anti-androgens.…”
Section: Introductionmentioning
confidence: 98%
“…This signaling is important for the development and maintenance of male sexual health (Fridmans et al 2005 ). Flutamide has been shown to cause reduced AGDs, increased nipple retention, pubertal delays, decreased sex organ weights, hypospadias and reduced penile length in male rat offspring (summarized in Fussell et al 2015 ) and prochloraz was found to increase transient nipple retentions and caused delayed entries into puberty (Christiansen et al 2009 ; Laier et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%